2002
DOI: 10.1093/jn/132.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Medium-Chain Triglycerides: Potential Agents in the Prevention of Obesity

Abstract: Medium chain fatty acids (MCFA) are readily oxidized in the liver. Animal and human studies have shown that the fast rate of oxidation of MCFA leads to greater energy expenditure (EE). Most animal studies have also demonstrated that the greater EE with MCFA relative to long-chain fatty acids (LCFA) results in less body weight gain and decreased size of fat depots after several months of consumption. Furthermore, both animal and human trials suggest a greater satiating effect of medium-chain triglycerides (MCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(225 citation statements)
references
References 24 publications
5
213
1
6
Order By: Relevance
“…Similarly, medium-chain triacylglycerol (MCT) enhances fat metabolism due to its distinct metabolic pathway. 27 Previous studies in humans show increased postprandial EE and fat oxidation after both acute 7 and repeated 28,29 MCT feeding, supporting the reduced weight gain observed with chronic 30 MCT consumption. St Onge et al reported that MCT increased fat oxidation and EE in a 4-week crossover feeding studies including both women 28 and men.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, medium-chain triacylglycerol (MCT) enhances fat metabolism due to its distinct metabolic pathway. 27 Previous studies in humans show increased postprandial EE and fat oxidation after both acute 7 and repeated 28,29 MCT feeding, supporting the reduced weight gain observed with chronic 30 MCT consumption. St Onge et al reported that MCT increased fat oxidation and EE in a 4-week crossover feeding studies including both women 28 and men.…”
Section: Discussionmentioning
confidence: 70%
“…caffeine, green tea catechins and medium-chain TAG) or that shift nutrient partitioning in favour of lean tissue (e.g. conjugated LA) has been demonstrated at much lower doses in humans (albeit adults) than in laboratory rodents (27,46,47) .…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…It is absorbed directly into the portal circulation and transported to the liver for rapid oxidation. This mechanism could increase energy expenditure, decrease their deposition into adipose tissue and result in faster satiety (St-Onge and Jones 2002).…”
Section: Introductionmentioning
confidence: 99%